Implementing national policing agendas and strategies for fraud at local level. Issue 4 (1st October 2018) - Doig, Alan
Abstract : Purpose: The purpose of this study is to assess, since the 2006 Fraud Review, recommendations, strategies and consequential organisational and other changes at national, regional and local levels relating to fraud, using the Northeast as a case study. It also notes that implementation may have been influenced by institutional changes and related emerging governmental policy agendas and institutional changes relating to organised crime, terrorism and cybercrime. Design/methodology/approach: The research for the paper was undertaken by desk reviews of primary and secondary material. The paper also involved face-to-face interviews with personnel from the regional fraud unit and the three North-east police forces' fraud units. The interviews were semi-structured and were conducted on grounds of anonymity for the personnel and the forces involved, with a focus on trends and issues. The personnel were invited to comment on a draft of the paper in terms of accuracy of the information they provided; no revisions or additions were proposed. Interpretation of that information is the sole responsibility of the author. Findings: The paper finds that, despite the decade since the Fraud Review, issues of effectiveness or relevance of national fraud strategies, absence of incentives and identifiable benefits and continuous influence of competing agendas on police priorities continue to marginalise fraud as a mainstream police function and limit the level of resource committed to what also continues to be a rising area of criminality. Research limitations/implications: The research looks at the recommendations, strategies and consequential organisational and other changes at national, regional and local levels through implementation by four policing units in the North-east. It also notes that implementation may have been influenced by institutional changes and related emerging governmental policy agendas and institutional changes relating to organised crime, terrorism and cybercrime. While the research is limited in that, it draws on the experience of three local and one regional fraud unit; its findings support further research about the implementation of strategies and agendas in practice on the ground. Practical implications: The research validates many of the findings by Her Majesty's Inspectorate of Constabulary (HMIC) and supports the need to review national strategies to ensure effective implementation at local level for what also continues to be a rising area of criminality. Social implications: The research raises important issues concerning public concern over fraud where majority of frauds are of high volume, low value with low levels of recovery and usually targeted at individuals but where the policing responses are targeted elsewhere. Originality/value: The research is the first study on the local implementation of national strategies on fraud and raises positive and less positive aspects of how far national strategies and intentions are addressed on the ground.